DESIGN OF AN IOT-BASED TEMPERATURE AND HUMIDITY MONITORING SYSTEM FOR EFFICIENT HVAC DATA COLLECTION IN AIRPORT - Habillah, M. Fathar (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Penerbangan Palembang, 2025)
The Airport Authority enforces thermal comfort regulations under Government Regulation PM 41 of 2023, which requires room temperatures to be maintained below 25°C in check-in areas, departure lounges, and baggage claims. However, temperature and humidity are recorded manually at Juanda International Airport, Surabaya. This research aims to develop an IoT-based system for real-time environmental monitoring and automated server logging. Using a Level 3 R&D approach with the ADDIE model and Focus Group Discussion (FGD) validation, the system was tested. It achieved a standard temperature deviation of 0.3162°C and a humidity deviation of 0.733% relative humidity (RH), meeting the requirements of ISO/IEC 17025 standards. The system streams data to Google Sheets, Blynk, and a custom web interface. Expert evaluations gave the system an average feasibility score of 86.76%, categorizing it as “Very Feasible.” These findings demonstrate the system’s accuracy, reliability, and potential for efficient airport HVAC monitoring and control.